Effect of intraarticular human umbilical cord mesenchymal stem cells transplantation on cartilage degradation and matrix metalloproteinases in OA rat model - Yanqun Li; Qipeng Han; Shayan Chen; Wenlong Huang; Yanqing Chen; Zhihuang Wu; Fengming Tan; Muyun Liu; Jiangying Zou (BMC Musculoskeletal Disorders)
Abstract Background Osteoarthritis (OA) is a common cause of disability around the world, but the pathophysiology is still poorly understood. The study sought to investigate the effects of umbilical cord mesenchymal stem cells (UC-MSCs) injection in OA, with a focus on cartilage degradation. Methods The serum matrix metalloproteinase (MMPs) and a disintegrin and metalloprotease domains with thrombospondins motifs (ADAMTS) levels in OA patients were examined using ELISA. The levels of MMPs and ADAMTS in peripheral blood mononuclear cells (PBMCs) following co-cultured with UC-MSC were determined by ELISA. The anterior cruciate ligament transection (ACLT) surgery was performed on the knee joints of a rat OA model, followed by intra-articular injection of UC-MSCs at 4 weeks and 8 weeks after surgery, and the changes of the severity of OA, tibiofemoral cartilage, and subchondral bone were observed by Safranin-O staining, hematoxylin and eosin (H&E) staining, and micro-CT imaging. Results OA patients showed the higher protein levels of MMP2, 9, 13, ADAMTS4 and 5 than healthy controls. Furthermore, in vitro incubation of PBMC derived from OA patients with UC-MSCs down-regulated the protein expression of these proteases. Positive correlations were observed between serum MMP9 levels and high-sensitivity C-reactive protein (hsCRP) in OA patients, while a negative correlation between serum MMP13 and Alkaline phosphatase (ALKP) was observed in these patients. There was a negative correlation between OA patients’ serum ADAMTS 4 and Lipoprotein (a)(Lp(a)). Western blotting and immunohistostaining were applied to assess the protein levels of matrix metalloproteinases and ADAMTSs in rat knee joints and these protein levels were significantly decreased in the UC-MSC intra-articular injection group. Micro-CT results showed in the OA rat model human UC-MSCs treatment alleviated the destruction of the tibial subchondral bone. Conclusion UC-MSCs decreased the level of several matrix proteases, slowing the progression of OA formation in rats. Our findings suggested that matrix metalloproteinases and ADAMTSs play a role in OA progression, UC-MSC exerted beneficial therapeutic effects on OA rat model by reducing the levels of these matrix metalloproteinases and ADAMTSs.